2014
DOI: 10.1080/03602559.2014.919647
|View full text |Cite
|
Sign up to set email alerts
|

The TiO2–Clay-LDPE Nanocomposite Packaging Films: Investigation on the Structure and Physicomechanical Properties

Abstract: The role of nanoclays and TiO 2 nanoparticle loadings were investigated on low density polyethylene crystalline structure, in addition to studying packaging film properties such as barrier, thermal and mechanical properties. The polymer crystal study indicated for the orthorhombic crystal phase and about 20% lower degree of crystallinity for nanocomposites containing more than 2 wt.% TiO 2 nanoparticles. Based on the X-ray diffraction technique, the dispersion of nanoclays was improved to almost good degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…24,25 Effectiveness of nanoparticles in barrier properties have been elaborated in many studies and extent of this enhancement can be influenced by many factors: for instance, the extent of nanoparticles dispersion in polymer matrix, which is the most important factor, type of polymer and nanoparticles and compatibilizer. 26,27 The significance of reduction in permeability is elucidated when obtained results were compared with the improvement achieved by other studies for gases, moisture and other volatile compounds. For instance, Dadbin et al reported the oxygen permeability reduction in a LDPE nanocomposite containing 5 wt% nanoclay.…”
Section: Water Vapour Permeabilitymentioning
confidence: 99%
“…24,25 Effectiveness of nanoparticles in barrier properties have been elaborated in many studies and extent of this enhancement can be influenced by many factors: for instance, the extent of nanoparticles dispersion in polymer matrix, which is the most important factor, type of polymer and nanoparticles and compatibilizer. 26,27 The significance of reduction in permeability is elucidated when obtained results were compared with the improvement achieved by other studies for gases, moisture and other volatile compounds. For instance, Dadbin et al reported the oxygen permeability reduction in a LDPE nanocomposite containing 5 wt% nanoclay.…”
Section: Water Vapour Permeabilitymentioning
confidence: 99%
“…Nanofillers have been proved to enhance the barrier properties of polymers, and to impart other additional benefits such as improvements in mechanical properties and weight reduction of the resulting nanocomposite packaging items . In this view, and in order to understand the diffusion phenomena and to develop new barrier materials, various research works were conducted to study the effectiveness of nanoclay incorporation into polymeric substrates to form barrier packaging materials . Most of the reported literature studies of such emerging materials only focused on the transport of gas molecules, mainly oxygen (O 2 ), carbon dioxide (CO 2 ), and water vapor .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of Cloisite®15A and Cloisite®20A on the O 2 , CO 2 , and water vapor barrier properties of different PE grades based nanocomposite systems was largely investigated during the last decades . For example, Dadfar et al reported that in LDPE/EVA blends filled with 2, 3, and 4 wt% Cloisite®15A, the oxygen permeability reduced by approximately 15%, 29%, and 44%, respectively as compared to neat LDPE.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations